Webinar “Mengenal Lebih Dekat Kekerasan pada Anak” Berhasil Meningkatkan Pengetahuan Masyarakat mengenai Kekerasan pada Anak - Fathiyyatul Khaira; Rahmani Welan; Westi Permata Wati; Noverika Windasari; Rizkia Chairani Asri; Fory Fortuna; Dwi Sabtika Julia; Septi Mayang Sarry; Satya Wydya Yenny (Warta Pengabdian Andalas, 2022)
Incidents of child abuse increase every year, including cases in West Sumatra. Violence experienced by children can cause physical disorders, impairment in cognitive, emotional, and social development, and discrimination in the social environment. The government has set rules regarding the protection of children against violence. Still, not all people know the forms of child abuse, their impact on children, and how to report child abuse cases. Therefore, we held a webinar, "Knowing more about child abuse," to educate people. One hundred three participants from various backgrounds attended this activity, but only 90 completed the pre-test and post-test questionnaires. Based on paired T-test, there was a significant increase in the mean score of participants' knowledge about emotional violence, sexual violence, and neglect/abandonment after the webinar (p<0.05). In addition, there was also an increase in the mean score of participants' knowledge about physical violence, although it was not statistically significant (p=0.103). In conclusion, education in webinars can increase public knowledge about child abuse.